Halophytes of Tersko-kumsk Lowland Area, Their Protection and Rational Use - Abdurzakova, A S; Astamirova, M A-M; Magomadova, R S; Israilova, S A; Khanaeva, Kh R; Khasueva, B A; Umaeva, A M; Shakhgirieva, Z I (KnE Life Sciences, 2019)
Article provides a brief analytical review of studies of halophilic flora species of Tersko- Kumsk lowland area. The most important representatives are indicated, the adaptive properties of different halophyte groups are considered. Their resource value is noted (fodder, medicinal, melliferous, tannic, etc.). In the systematic aspect, the halophilic flora exhibits Mediterranean features, dicotyledons dominate in it, club-moss and horsetails are completely absent, ferns are minimally present. In the edaphic relation, most species of halophytes are obligate, confined to one type of substrate, and the vast majority of halophytes are confined to the steppe belt, the subalpine belt, the belt of upland xerophytes and the alpine belt are in descending order, least of all halophytes in the forest belt, individual species live in subnival belt.The question of the protection of solonchak vegetation and solonchak steppes as a peculiar ecosystems, with a distinctive landscape and original flora containing a highly specialized ecological group of plants, which testifies to the relationship of the nature of plants with the environment. Halophilic cenoses can serve as indicators of the soil, chemical composition and depth of groundwater.